DC electrical stimulation enhances proliferation and differentiation on N2a and MC3T3 cell lines - Daniel Martín; J. Bocio-Nuñez; Santiago F. Scagliusi; Pablo Pérez; Gloria Huertas; Alberto Yúfera; Mercè Giner; Paula Daza (Journal of Biological Engineering, 2022)
Abstract Background Electrical stimulation is a novel tool to promote the differentiation and proliferation of precursor cells. In this work we have studied the effects of direct current (DC) electrical stimulation on neuroblastoma (N2a) and osteoblast (MC3T3) cell lines as a model for nervous and bone tissue regeneration, respectively. We have developed the electronics and encapsulation of a proposed stimulation system and designed a setup and protocol to stimulate cell cultures. Methods Cell cultures were subjected to several assays to assess the effects of electrical stimulation on them. N2a cells were analyzed using microscope images and an inmunofluorescence assay, differentiated cells were counted and neurites were measured. MC3T3 cells were subjected to an AlamarBlue assay for viability, ALP activity was measured, and a real time PCR was carried out. Results Our results show that electrically stimulated cells had more tendency to differentiate in both cell lines when compared to non-stimulated cultures, paired with a promotion of neurite growth and polarization in N2a cells and an increase in proliferation in MC3T3 cell line. Conclusions These results prove the effectiveness of electrical stimulation as a tool for tissue engineering and regenerative medicine, both for neural and bone injuries. Bone progenitor cells submitted to electrical stimulation have a higher tendency to differentiate and proliferate, filling the gaps present in injuries. On the other hand, neuronal progenitor cells differentiate, and their neurites can be polarized to follow the electric field applied.